ANALYSIS OF THE IMPACT OF THE PROPORTION OF INDEPENDENT COMMISSIONERS, LEVERAGE, AND SIZE ON THE ACCOUNTING CONSERVATISM OF STATE-OWNED ENTERPRISES (BUMN) - Sri Wahjuni Latifah; Saskiya Sasa Difananda (Jurnal Akuntansi, 2021)
This study intends to analyze the Impact of the Proportion of Independent Commissioners, Leverage, and Size on the Accounting Conservatism in State-Owned Enterprises (BUMN) listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period. Based on these objectives, there are important questions in this study: whether the variables of the Proportion of Independent Commissioners, Leverage, and size as independent variables impact accounting conservatism, which is the dependent variable. To answer this question, the researcher used the multiple linear regression analysis methods using the Stata15 application. Determination of the sample in this study using purposive sampling method based on specific criteria and the sample obtained is 51 company data. There are several implications in this study, namely theoretical implications and practical implications. Theoretically, this research can be a reference for further researchers in analyzing the effect of accounting conservatism. While practically, it can have implications for company management, especially in decision making, for investors in terms of consideration when making investments and creditors related to the company’s credit activities. The results showed that the leverage variable impacted accounting conservatism, while the proportion of independent commissioners and size had no impact on accounting conservatism.